Natural alternatives to corticosteroids in anti-oedema therapy - Palmieri, Giancarlo (Progress in Nutrition, 2017)
Adrenal cortical steroids are molecules produced and released by the adrenal cortex. They are frequently employed in clinical practice, in varying quantity, depending on the pathology at issue, for the treatment of numerous immunoinflammatory and neoplastic disorders. [...]